HIGHER EDUCATION IN RUSSIA: ACHIEVEMENTS, PROBLEMS, PROSPECTS - Alexander P. Egorshin; Irina V. Gus’Kova (Высшее образование в России, 2016)
The article is devoted to the analysis of development of education system in Russia for the last 25 years. The article adduces statistics of quantity dynamics of higher educational institutions and the number of the faculty and students. Assessment of the reforming processes of the education system in Russia is given. There are also viewed the key problems of the procedure of licensing and accreditation of a higher educational institution.Reasonable suggestions on reforming the system of managing Russian education and itsfinancing are provided in the conclusion. Some special recommendations apply to the financial management of higher educational institutions.